« ‘This, I told myself, was really Africa’. Des territoires et des femmes. Récits féminins de voyage en Afrique Australe à la fin du XIXe siècle » - Ludmila Ommundsen (Revue LISA)
In Victorian Britain, travel writing was informed by an unprecedented colonial expansion – in particular, the “scramble for Africa” – and the rise of the women’s movement in the late 19th century. Fuelled by the notions of motherhood and domesticity that characterized late imperial society, the presence of women in colonies served the purpose of domesticating the South. Yet, as geographical conquest merges with sexual conquest, the narratives of some female travellers in Southern Africa unveil unexpected territories that manifest specific territorialities. Although conjuring up feminist utopias, weren’t these female writers trying to construct a conspicuous literary ghetto ?